Long-term changes in global socioeconomic benefits of flood defenses and residual risk based on CMIP5 climate models - Lim, W; Yamazaki, D; Koirala, S; Hirabayashi, Y; Kanae, S; Dadson, S; Hall, J; Sun, F (Wiley, 2018)
A warmer climate is expected to accelerate the global hydrological cycle, causing more intense precipitation and floods. Despite recent progress in global flood risk assessment, the socioeconomic benefits of flood defenses (i.e., reduction in population/economic exposure) and the residual risk (i.e., residual population/economic exposure) are poorly understood globally and regionally. To address these knowledge gaps, we use the runoff data from a baseline and 11 CMIP5 climate models to drive the CaMa‐Flood model incorporating the latest satellite‐river width information. From the simulated annual maxima, we use a Gumbel distribution to estimate the river water depth ‐ flood return period relationship. We independently evaluate flood impacts on population and economy (i.e., gross domestic product (GDP)) for a range of flood return periods. We estimate the socioeconomic benefits and the corresponding residual risk for the globe and 26 sub‐continental regions. The global population (GDP) exposed to flooding is ∼8% (∼7%) per year lower when implementing existing flood protection infrastructure extracted from the FLOPROS database. If the current flood defenses were to be unchanged in the future (RCP4.5 and RCP8.5, i.e., ∼2‐∼4.3°C above the pre‐industrial levels), the globe and most of the regions (particularly where developing countries are concentrated) would experience an increase in residual risk. This increase is especially obvious when the gap of climate forcing between RCP8.5 and RCP4.5 widens by end of the 21st century. We finally evaluate the impact of changed flood defense levels on the socioeconomic benefits and the corresponding residual risk.